The effect of Trichomnas Muris parasite on some blood standards in mice. - Azhar abbas Ashour (Tikrit Journal of Pure Science, 2020)
This study was conducted in College of Science, University of Mosul, it aims to identify the intestinal parasites that affect  mice and their effect, this was done by collecting 37 mice, 22 of which were used as a control group, when a microscopic examination of the contents of the intestines of these animals is observed the presence of parasites Triohomonas Muris, during the period 2l10l2019 to 20l1l2020.